Proposed sanitation for a timber house constructed on water - Mazandarani, Navid Nasrolah; Ibrahim, Rahinah; Mohammad, Thamer Ahmed; Idris, Azni; Ismail, Muhamad Syahrul Efendi (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
One of the problems causing a threat to public health is the sanitation system of timber houses built in water. The sanitation systems of these houses unfortunately dispose wastes directly into the natural water bodies, since the houses are not actually equipped with the proper sanitation system for disposing wastes from the toilets. The centralization of the waste disposal system is not used widely at tourist areas constructed on water due to technical and financial difficulties. This research requires gathering relevant data from various sources. Moreover, this project will utilize qualitative data collection tools, but is rooted in a qualitative epistemological position that signifies the importance of locating the research within a particular social and cultural house settlement. This paper surveys the literature on problems that arise from raw sewerage disposed into natural water bodies before any sanitation is proposed to solve the problem and how an individual sewage treatment plant can be installed and solve this problem. A sustainable potential solution through making use of a new individual sewage treatment plant for Timber houses is presented in this proposal. The results would lead to the development of affordable waste management systems, as well as, improvement of water quality surrounding the Timber houses while maintaining the social and cultural values of indigenous people living in them. In this study, a sanitation system is proposed to be used in the timber houses constructed in water and the system was tested and showed that it is effective in wastewater treatment.